The Effect of Father’s Involvement in Parenting on Emotional Regulation in Catholic Adolescent at North Jakarta - Gregorius Alexander Kristianto; Ratriana Yuliastuti Endang Kusumiati (Universitas PGRI Yogyakarta, 2026)
This study examined the effect of father involvement in parenting on emotion regulation among Catholic adolescents in Region VIII of the Holy Cross Parish, North Jakarta. A quantitative causal-comparative design was employed. Participants were 30 adolescents selected through a total sampling. Data were collected using questionnaires measuring father involvement and adolescents’ emotion regulation. Data analysis was conducted using simple linear regression. Descriptive findings showed that father involvement was generally moderate to high, while adolescents demonstrated high levels of emotion regulation. However, regression analysis indicated no statistically significant effect of father involvement on emotion regulation (p = .910). The coefficient of determination was very small (R² = .001), indicating that father involvement explained a low proportion of variance in emotion regulation. These results suggest that adolescents’ emotion regulation may be more strongly influenced by other factors, including maternal caregiving, peer relationships, and the religious community environment. Despite the non-significant findings and the small sample size, this study highlights the importance of contextual and cultural considerations in examining parenting processes. It contributes to family and parenting psychology by emphasizing adolescent emotion regulation. Keywords: adolescent, emotion regulation, father involvement, parenting